2000
DOI: 10.1017/s0033291799002007
|View full text |Cite
|
Sign up to set email alerts
|

Right lower prefronto-parietal cortical dysfunction in akinetic catatonia: a combined study of neuropsychology and regional cerebral blood flow

Abstract: Findings are preliminary but suggest right lower prefronto-parietal cortical dysfunction in catatonia, which may be closely related to psychomotor disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…The prefrontal cortex seems to play a critical role in catatonia according to neuroimaging studies [70][71][72] and the observation that benzodiazepines might treat some catatonic symptoms by activating GABAergic neurons of this area [73]. Interestingly, the few rTMS cases for catatonia have also targeted the prefrontal areas [74][75][76], suggesting that this might be a suitable area for catatonia treatment, especially in the context of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The prefrontal cortex seems to play a critical role in catatonia according to neuroimaging studies [70][71][72] and the observation that benzodiazepines might treat some catatonic symptoms by activating GABAergic neurons of this area [73]. Interestingly, the few rTMS cases for catatonia have also targeted the prefrontal areas [74][75][76], suggesting that this might be a suitable area for catatonia treatment, especially in the context of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…However, single case reports noted reduced bilateral frontal CBF [156] or hypometabolism [157], along with bilateral thalamic hypermetabolism [157]. Similarly, the case series of Northoff et al [129,158] of a mixed-diagnosis catatonia group (3/10 with schizophrenia) revealed hypoperfusion in the middle and right lower prefrontal cortex. The finding was corroborated by functional magnetic resonance imaging (fMRI) demonstrating hypoactivation of M1 during a sequential finger opposition task in akinetic patients [159,160].…”
Section: Neurobiology Of the Motor System In Schizophreniamentioning
confidence: 99%
“…Still, due to small samples with heterogeneous catatonic symptoms, the pathobiology of catatonia remains widely unknown. Case reports of brain perfusion during catatonia have revealed conflicting results (Galynker et al, 1997;Northoff et al, 2000;Tsujino et al, 2011). As many catatonic syndromes present with fluctuating and alternating signs such as agitation shifting into akinesia and back (Ungvari et al, 2010), the motor system in catatonia is likely to experience varying states of excitation.…”
Section: Catatoniamentioning
confidence: 99%